(untitled) (Jurnal Biologi dan Pembelajarannya (JB&P), 2022)
kar kaik-kaik (Uncaria cordata (Lour.) Merr.) is a medicinal plant used for generations by the Dayak tribe to treat diarrhea and dysentery. This study aims to determine the total flavonoid content and antioxidant activity of the active fraction of kaik-kaik root leaves which have the potential to cure diarrhea. Kaikkaik root leaf extract was made by maceration using 70% ethanol. Total flavonoid test was carried out using UV-VIS spectrophotometry with quercetin standard. The results showed that the ethanol fraction had the highest flavonoid content, namely9.08 mg QE/g sample,n-hexane fraction of 5.21mg QE/g sample and ethyl acetate fraction of 3.54 mg QE/g. Testing of antioxidant activity using the DPPH method. The results showed that the ethanol fraction had a very strong antioxidant activity of 49.22 ppm, the n-hexane fraction had a moderate antioxidant activity of 108.22 ppm and the ethyl acetate fraction had a moderate antioxidant activity of 130.30. The total flavonoid content and antioxidant activity of the kaik-kaik root leaf extract indicate that the kaik-kaik root leaf extract has the potential to be developed into herbal medicine to treat diarrhea.